European Citizenship: Theories, Arenas, Levels - Foradori, Paolo; Piattoni, Simona; Scartezzini, Riccardo (Nomos Verlagsgesellschaft mbH & Co. KG, 2007)
This book addresses the fundamental question of the social foundations of the European Union by looking at the concept of citizenship. It argues that citizenship, rather than identity, is the most promising anchor for developing a true European "community of destiny" rather than just of policies. It begins by discussing the theoretical and normative underpinnings of this concept and by drawing the contours of a possible notion of citizenship when applied to a multi-level polity such as the European Union. It then explores the arenas within which such a notion may be practically shaped in a "bottom-up" approach to the construction of citizenship rights, through more or less momentous choices made by actors both within and without European institutions. Finally it traces the historical roots of the concept of citizenship and explores the multiple levels at which it can be predicated, thus addressing the specific feature of the European Union of being a multi-level polity. The reflections herein contained aim at providing guidance to the architects of European citizenship, be they active members of civil society as well as top-level decision-makers.